POLA ASUH ORANG TUA ANAK USIA 5-6 TAHUN KELAS B2 DI TK SANTA GEMMA SEKADAU - Oktaviani, Nindi (DUNIA ANAK: Jurnal Pendidikan Anak Usia Dini, 2024)
This research is motivated by the fact that most of the students' parents (father and mother) are workers so there is not enough time to take care of their children. The purpose of this study is to describe the parenting patterns applied by parents of 5-6 years old children in class B2 at Santa Gemma Kindergarten. The resource persons in this study were 10 children and 10 parents, this research used a qualitative approach with a descriptive form. The data collection technique uses observation, interview, and documentation techniques. Data analysis techniques using the Miles and Huberman model which consists of data collection, data reduction, data presentation and verification. Based on the results of the study, it can be seen that the parenting patterns applied by parents of children aged 5-6 years in class B2 at Santa Gemma Sekadau Kindergarten show that of the 10 parents studied, 1 parent applies authoritarian parenting and 9 parents apply democratic parenting. Factors that influence parenting patterns are parents' parenting background, education level, economic status, and parents' occupation. Efforts that have been made by parents in parenting children are exemplary, discipline, habituation, and creating a conducive atmosphere that is fun for children. Based on the results of this study, it can be concluded that there are 9 parents who apply democratic parenting patterns and 1 parent who applies authoritarian parenting patterns to children aged 5-6 years in class B2 at Santa Gemma Sekadau Kindergarten.